De LIBOR a SOFR. Nuevas tasas de referencia en los tiempos del bicentenario - Pérez Vargas, Víctor (2026)
This article refers to the possible solutions to the problem that there are many contracts that did not foresee the contingency of the disappearance of the LIBOR rate. This is what is called an Arising Contractual Loophole (on the reference rate). The possibility that the LIBOR rate will cease to be published in the future poses a problem at the contractual level for those credit contracts, the interest rate of which is referenced to the LIBOR rate, and do not have an alternative rate foreseen in the event that, for reasons beyond the parties’ control, it is not possible to use the LIBOR rate.